A calcium sulfate whisker reinforced PVC board and its preparation process

By introducing calcium sulfate whiskers and nanocopper composites into the PVC plate, loading iron tetraoxide on graphene oxide and performing chitosan intercalation treatment, the limitations of traditional PVC materials in terms of strength, toughness and flame retardancy are solved, and the mechanical properties and flame retardancy of the PVC plate are significantly improved.

CN119220031BActive Publication Date: 2025-03-04JIANGXI FENGZHU NEW MATERIAL TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411516063.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-03-04
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

Traditional PVC materials have limitations in strength, toughness and flame retardancy, limiting their use in high-performance applications.

Method used

By introducing calcium sulfate whiskers and nanocopper composites into the PVC plate, loading iron tetraoxide on graphene oxide, and undergoing chitosan intercalation treatment, the mechanical properties and flame retardancy of the PVC plate are improved.

Benefits of technology

It significantly improves the mechanical properties and flame retardancy of PVC plates, improves its thermal stability and processing properties, and reduces the weight of the plate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a calcium sulfate whisker reinforced PVC board and a preparation process thereof, and relates to the technical field of PVC boards. The invention introduces calcium sulfate whiskers into PVC materials, and the calcium sulfate whiskers have a low density, which helps to reduce the weight of the PVC board. The calcium sulfate whiskers show excellent stability under high temperature conditions and can improve the thermal stability of PVC. The invention loads ferroferric oxide on graphene oxide, improves the flame retardancy of the graphene, and then uses chitosan to perform intercalation treatment on it, thereby increasing the interlayer spacing of the graphene loaded with ferroferric oxide, so that it has more specific surface area to load the calcium sulfate whisker-nano copper complex, improves the dispersibility of the calcium sulfate whisker-nano copper complex, and thus enhances the mechanical properties and flame retardancy of the PVC board.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PVC boards, in particular to a calcium sulfate whisker reinforced PVC board and a preparation process thereof. Background Art

[0002] With the rapid development of the plastics industry, polyvinyl chloride, as a widely used synthetic resin material, is widely used in the fields of construction, automobiles, electronics and packaging due to its excellent chemical resistance, formability and economy. However, traditional PVC materials have certain limitations in terms of strength, toughness and flame retardancy, which restricts their use in high-performance applications. In order to improve the mechanical properties and thermal stability of PVC, the existing technology introduces fillers into PVC materials. The introduction of fillers can not only significantly improve the strength and rigidity of PVC boards, but also improve their heat resistance and processing properties, but the flame retardant properties of PVC boards need to be further strengthened.

[0003] In order to solve the above problems and improve the mechanical properties and flame retardancy of PVC boards, the present invention provides a calcium sulfate whisker reinforced PVC board and a preparation process thereof. Summary of the invention

[0004] The object of the present invention is to provide a calcium sulfate whisker reinforced PVC board and a preparation process thereof, so as to solve the problems raised in the prior art.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A preparation process of a calcium sulfate whisker reinforced PVC board comprises the following steps:

[0007] Step 1: Take modified graphene oxide and deionized water, perform ultrasonic dispersion, add calcium sulfate whisker-nano copper composite, stir evenly, heat to 60-65° C., react for 4-5 hours, wash and dry to obtain calcium sulfate whisker-graphene composite;

[0008] Step 2: taking PVC resin A, hyperbranched polyamide ester, chlorinated polyethylene, oxidized polyethylene wax, zinc stearate, hydrotalcite, and calcium sulfate whisker-graphene composite, stirring at 80-85° C. for 25-30 min, and cooling to obtain a skin layer mixture;

[0009] Step 3: Take PVC resin B, chlorinated polyethylene, calcium carbonate, hydrotalcite, azodicarbonamide, oxidized polyethylene wax, and zinc stearate, stir at 90-95° C. for 10-12 minutes, and cool to obtain a core layer mixture;

[0010] Step 4: The core layer mixture and the skin layer mixture are extruded, cooled, pulled and cut simultaneously to obtain a PVC board.

[0011] More optimally, the preparation method of the calcium sulfate whisker-nano copper composite is: take calcium sulfate whisker, deionized water, and anhydrous ethanol, stir evenly, heat to 55-60°C, add ammonia water, adjust the pH value to 8-9, add γ-aminopropyltriethoxysilane, react for 1-2h, heat to 80-85°C, react for 1-2h, cool to 40-45°C, add copper sulfate solution, react for 1-2h, filter, add deionized water, stir evenly, heat to 70-75°C, add sodium hydroxide solution, adjust the pH value to 10, add hydrazine hydrate, react for 1-2h, filter, wash, and dry to obtain the calcium sulfate whisker-nano copper composite.

[0012] More optimally, the preparation method of the modified graphene oxide is: take graphene loaded with ferroferric oxide and deionized water, ultrasonically disperse to obtain a graphene solution loaded with ferroferric oxide; take chitosan and deionized water, stir evenly, add hydrochloric acid dropwise, stir for 30-40 minutes, add ammonia water dropwise, adjust the pH value to 3.5-4, add the graphene solution loaded with ferroferric oxide, heat to 55-60°C, react for 1-2 hours, wash and dry to obtain modified graphene oxide.

[0013] More optimally, the preparation method of the graphene loaded with ferroferric oxide is: take graphene oxide and deionized water, ultrasonically disperse, add ferric chloride hexahydrate and ferrous sulfate heptahydrate, heat to 60-65°C under nitrogen protection, add ammonia water, adjust the pH value to 9-10, heat to 65-70°C, react for 3-5h, wash and dry to obtain graphene loaded with ferroferric oxide.

[0014] More optimally, the preparation method of the hyperbranched polyamide ester is: take diethanolamine and N,N-dimethylacetamide, stir evenly to obtain a diethanolamine solution; take succinic anhydride and N,N-dimethylacetamide, stir evenly, pass nitrogen, and then add the diethanolamine solution at 0-1°C, react for 8-10 hours to obtain compound A; take compound A, add p-toluenesulfonic acid, react at 120-125°C for 7-8 hours, extract, stand, and dry to obtain a hyperbranched polyamide ester.

[0015] More optimally, the skin layer mixture includes the following ingredients, by weight: 70-80 parts of PVC resin A, 2-3 parts of hyperbranched polyamide ester, 4-5 parts of chlorinated polyethylene, 0.2-0.6 parts of oxidized polyethylene wax, 0.1-0.3 parts of zinc stearate, 2-3 parts of hydrotalcite, and 7-8 parts of calcium sulfate whisker-graphene composite.

[0016] More optimally, the core layer mixture includes the following ingredients, by weight: 65-70 parts of PVC resin B, 4-5 parts of chlorinated polyethylene, 15-20 parts of calcium carbonate, 2-3 parts of hydrotalcite, 1-2 parts of azodicarbonamide, 0.2-0.6 parts of oxidized polyethylene wax, and 0.1-0.3 parts of zinc stearate.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] (1) The present invention introduces calcium sulfate whiskers into the PVC material. The calcium sulfate whiskers have a low density, which helps to reduce the weight of the PVC board. The calcium sulfate whiskers show excellent stability under high temperature conditions and can improve the thermal stability of PVC.

[0019] (2) The present invention loads ferroferric oxide on graphene oxide to improve the flame retardancy of graphene, and then uses chitosan to perform intercalation treatment on it, thereby increasing the interlayer spacing of the graphene loaded with ferroferric oxide, so that it has more specific surface area to load the calcium sulfate whisker-nano copper composite, thereby improving the dispersibility of the calcium sulfate whisker-nano copper composite, thereby enhancing the mechanical properties and flame retardancy of the PVC board.

[0020] (3) The present invention prepares a calcium sulfate whisker-nano copper composite by adding a copper sulfate solution and then reducing it. The loading of nano copper improves the mechanical properties and flame retardancy of the PVC board.

[0021] (4) The present invention prepares a hyperbranched polyamide ester having a hydroxyl terminal group, and uses the hyperbranched polyamide ester to modify PVC resin, thereby enhancing the mechanical properties of the PVC resin. The terminal hydroxyl groups on the hyperbranched polyamide ester can react with the hydroxyl groups on the calcium sulfate whisker-graphene composite, thereby enhancing the compatibility of the calcium sulfate whisker-graphene composite in the mixture, thereby enhancing the mechanical properties and flame retardancy of the PVC board. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] The sources and models of the raw materials involved in the present invention are not subject to any special restrictions, and exemplary examples include: graphene oxide: can be purchased from Merck, model: 796034; calcium carbonate: particle size: 3500 mesh; hydrotalcite: 0.5-1µm; chlorinated polyethylene: can be purchased from Hubei Rishengchang New Material Technology Co., Ltd., model: 63231-66-3; PVC resin A: can be purchased from Axiall, USA, model: 8400; PVC resin B: can be purchased from Axiall, USA, model: 8542.

[0024] Embodiment 1: A process for preparing a calcium sulfate whisker reinforced PVC board, comprising the following steps:

[0025] Step 1: Preparation of hyperbranched polyamide ester:

[0026] Take 5.5g of diethanolamine and 15mL of N,N-dimethylacetamide, stir evenly to obtain a diethanolamine solution; take 7g of succinic anhydride and 15mL of N,N-dimethylacetamide, stir evenly, pass nitrogen, then add the diethanolamine solution at 0°C, react for 9h, and obtain compound A; take 10g of compound A, add 0.2g of p-toluenesulfonic acid, react at 122°C for 7.5h, extract, stand, and dry to obtain hyperbranched polyamide ester;

[0027] Step 2: Preparation of modified graphene oxide:

[0028] Take 0.2 g of graphene oxide and 200 mL of deionized water, disperse by ultrasonication, add 1.2 g of ferric chloride hexahydrate and 0.65 g of ferrous sulfate heptahydrate, heat to 62 ° C under nitrogen protection, add 25% ammonia water, adjust the pH value to 9.5, heat to 67 ° C, react for 4 h, wash and dry to obtain graphene loaded with ferrosoferric oxide;

[0029] Take 0.2g of graphene loaded with ferroferric oxide and 100mL of deionized water, and disperse them by ultrasonication to obtain a graphene solution loaded with ferroferric oxide; take 0.3g of chitosan and 20mL of deionized water, stir evenly, drop 0.2mL of 36% hydrochloric acid, stir for 35min, drop ammonia water, adjust the pH value to 3.8, add the graphene solution loaded with ferroferric oxide, heat to 58°C, react for 1.5h, wash and dry to obtain modified graphene oxide;

[0030] Step 3: Preparation of calcium sulfate whisker-nano copper composite:

[0031] Take 3g of calcium sulfate whisker, 35mL of deionized water, and 1g of anhydrous ethanol, stir evenly, heat to 57°C, add 25% ammonia water, adjust the pH value to 8.5, add 0.5g of γ-aminopropyltriethoxysilane, react for 1.5h, heat to 82°C, react for 1.5h, cool to 42°C, add 3.5mL of 0.8mol / L copper sulfate solution, react for 1.5h, filter, add 100mL of deionized water, stir evenly, heat to 72°C, add 10mol / L of sodium hydroxide solution, adjust the pH value to 10, add 1g of hydrazine hydrate, react for 1.5h, filter, wash, and dry to obtain a calcium sulfate whisker-nano copper composite;

[0032] Step 4: Preparation of calcium sulfate whisker-graphene composite:

[0033] Take 0.1 g of modified graphene oxide and 200 mL of deionized water, disperse by ultrasonication, add 2 g of calcium sulfate whisker-nano copper composite, stir evenly, heat to 62° C., react for 4.5 h, wash and dry to obtain a calcium sulfate whisker-graphene composite;

[0034] Step 5: Preparation of PVC board:

[0035] PVC resin A, hyperbranched polyamide ester, chlorinated polyethylene, oxidized polyethylene wax, zinc stearate, hydrotalcite, and calcium sulfate whisker-graphene composite were stirred at 82° C. for 28 min and cooled to obtain a skin layer mixture;

[0036] Take PVC resin B, chlorinated polyethylene, calcium carbonate, hydrotalcite, azodicarbonamide, oxidized polyethylene wax, and zinc stearate, stir at 92°C for 11 minutes, and cool to obtain a core layer mixture;

[0037] The core layer mixture is added into the main conical twin-screw extruder, and the skin layer mixture is added into the auxiliary conical twin-screw extruder, and extruded, cooled, pulled and cut at the same time to obtain a PVC board;

[0038] The skin layer mixture comprises the following ingredients, by weight: 75 parts of PVC resin A, 2.5 parts of hyperbranched polyamide ester, 4.5 parts of chlorinated polyethylene, 0.4 parts of oxidized polyethylene wax, 0.2 parts of zinc stearate, 2.5 parts of hydrotalcite, and 7.5 parts of calcium sulfate whisker-graphene composite;

[0039] The core layer mixture includes the following components, by weight: 67 parts of PVC resin B, 4.5 parts of chlorinated polyethylene, 18 parts of calcium carbonate, 2.5 parts of hydrotalcite, 1.5 parts of azodicarbonamide, 0.4 parts of oxidized polyethylene wax, and 0.2 parts of zinc stearate.

[0040] Embodiment 2: A process for preparing a calcium sulfate whisker reinforced PVC board, comprising the following steps:

[0041] Step 1: Preparation of hyperbranched polyamide ester:

[0042] Take 5.5g of diethanolamine and 15mL of N,N-dimethylacetamide, stir evenly to obtain a diethanolamine solution; take 7g of succinic anhydride and 15mL of N,N-dimethylacetamide, stir evenly, pass nitrogen, then add the diethanolamine solution at 0°C, react for 8h, and obtain compound A; take 10g of compound A, add 0.2g of p-toluenesulfonic acid, react at 120°C for 7h, extract, stand, and dry to obtain hyperbranched polyamide ester;

[0043] Step 2: Preparation of modified graphene oxide:

[0044] Take 0.2g of graphene oxide and 200mL of deionized water, disperse by ultrasonication, add 1.2g of ferric chloride hexahydrate and 0.65g of ferrous sulfate heptahydrate, heat to 60°C under nitrogen protection, add 25% ammonia water dropwise, adjust the pH value to 9, heat to 65°C, react for 3h, wash and dry to obtain graphene loaded with ferrosoferric oxide;

[0045] Take 0.2g of graphene loaded with ferroferric oxide and 100mL of deionized water, and disperse them by ultrasonication to obtain a graphene solution loaded with ferroferric oxide; take 0.3g of chitosan and 20mL of deionized water, stir evenly, drop 0.2mL of 36% hydrochloric acid, stir for 30min, drop ammonia water, adjust the pH value to 3.5, add the graphene solution loaded with ferroferric oxide, heat to 55°C, react for 1h, wash and dry to obtain modified graphene oxide;

[0046] Step 3: Preparation of calcium sulfate whisker-nano copper composite:

[0047] Take 3g of calcium sulfate whisker, 35mL of deionized water, and 1g of anhydrous ethanol, stir evenly, heat to 55°C, add 25% ammonia water, adjust the pH value to 8, add 0.5g of γ-aminopropyltriethoxysilane, react for 1h, heat to 80°C, react for 1h, cool to 40°C, add 3.5mL of 0.8mol / L copper sulfate solution, react for 1h, filter, add 100mL of deionized water, stir evenly, heat to 70°C, add 10mol / L of sodium hydroxide solution, adjust the pH value to 10, add 1g of hydrazine hydrate, react for 1h, filter, wash, and dry to obtain a calcium sulfate whisker-nano copper composite;

[0048] Step 4: Preparation of calcium sulfate whisker-graphene composite:

[0049] Take 0.1 g of modified graphene oxide and 200 mL of deionized water, disperse by ultrasonication, add 2 g of calcium sulfate whisker-nano copper composite, stir evenly, heat to 60° C., react for 4 h, wash and dry to obtain calcium sulfate whisker-graphene composite;

[0050] Step 5: Preparation of PVC board:

[0051] PVC resin A, hyperbranched polyamide ester, chlorinated polyethylene, oxidized polyethylene wax, zinc stearate, hydrotalcite, and calcium sulfate whisker-graphene composite were stirred at 80° C. for 25 min and cooled to obtain a skin layer mixture;

[0052] Take PVC resin B, chlorinated polyethylene, calcium carbonate, hydrotalcite, azodicarbonamide, oxidized polyethylene wax, and zinc stearate, stir at 90°C for 10 minutes, and cool to obtain a core layer mixture;

[0053] The core layer mixture is added into the main conical twin-screw extruder, and the skin layer mixture is added into the auxiliary conical twin-screw extruder, and extruded, cooled, pulled and cut at the same time to obtain a PVC board;

[0054] The skin layer mixture comprises the following ingredients, by weight: 70 parts of PVC resin A, 2 parts of hyperbranched polyamide ester, 4 parts of chlorinated polyethylene, 0.2 parts of oxidized polyethylene wax, 0.1 parts of zinc stearate, 2 parts of hydrotalcite, and 7 parts of calcium sulfate whisker-graphene composite;

[0055] The core layer mixture includes the following components, by weight: 65 parts of PVC resin B, 4 parts of chlorinated polyethylene, 15 parts of calcium carbonate, 2 parts of hydrotalcite, 1 part of azodicarbonamide, 0.2 parts of oxidized polyethylene wax, and 0.1 parts of zinc stearate.

[0056] Embodiment 3: A process for preparing a calcium sulfate whisker reinforced PVC board, comprising the following steps:

[0057] Step 1: Preparation of hyperbranched polyamide ester:

[0058] Take 5.5g of diethanolamine and 15mL of N,N-dimethylacetamide, stir evenly to obtain a diethanolamine solution; take 7g of succinic anhydride and 15mL of N,N-dimethylacetamide, stir evenly, pass nitrogen, then add the diethanolamine solution at 1°C, react for 10h, and obtain compound A; take 10g of compound A, add 0.2g of p-toluenesulfonic acid, react at 125°C for 8h, extract, stand, and dry to obtain hyperbranched polyamide ester;

[0059] Step 2: Preparation of modified graphene oxide:

[0060] Take 0.2 g of graphene oxide and 200 mL of deionized water, disperse by ultrasonication, add 1.2 g of ferric chloride hexahydrate and 0.65 g of ferrous sulfate heptahydrate, heat to 65 ° C under nitrogen protection, add 25% ammonia water dropwise, adjust the pH value to 10, heat to 70 ° C, react for 5 h, wash and dry to obtain graphene loaded with ferrosoferric oxide;

[0061] Take 0.2g of graphene loaded with ferroferric oxide and 100mL of deionized water, and perform ultrasonic dispersion to obtain a graphene solution loaded with ferroferric oxide; take 0.3g of chitosan and 20mL of deionized water, stir evenly, drop 0.2mL of 36% hydrochloric acid, stir for 40min, drop ammonia water, adjust the pH value to 4, add the graphene solution loaded with ferroferric oxide, heat to 60°C, react for 2h, wash and dry to obtain modified graphene oxide;

[0062] Step 3: Preparation of calcium sulfate whisker-nano copper composite:

[0063] Take 3g of calcium sulfate whisker, 35mL of deionized water, and 1g of anhydrous ethanol, stir evenly, heat to 60°C, add 25% ammonia water, adjust the pH value to 9, add 0.5g of γ-aminopropyltriethoxysilane, react for 2h, heat to 85°C, react for 2h, cool to 45°C, add 3.5mL of 0.8mol / L copper sulfate solution, react for 2h, filter, add 100mL of deionized water, stir evenly, heat to 75°C, add 10mol / L of sodium hydroxide solution, adjust the pH value to 10, add 1g of hydrazine hydrate, react for 2h, filter, wash, and dry to obtain a calcium sulfate whisker-nano copper composite;

[0064] Step 4: Preparation of calcium sulfate whisker-graphene composite:

[0065] Take 0.1 g of modified graphene oxide and 200 mL of deionized water, disperse by ultrasonication, add 2 g of calcium sulfate whisker-nano copper composite, stir evenly, heat to 65° C., react for 5 h, wash and dry to obtain calcium sulfate whisker-graphene composite;

[0066] Step 5: Preparation of PVC board:

[0067] PVC resin A, hyperbranched polyamide ester, chlorinated polyethylene, oxidized polyethylene wax, zinc stearate, hydrotalcite, and calcium sulfate whisker-graphene composite were stirred at 85° C. for 30 min and cooled to obtain a skin layer mixture;

[0068] Take PVC resin B, chlorinated polyethylene, calcium carbonate, hydrotalcite, azodicarbonamide, oxidized polyethylene wax, and zinc stearate, stir at 95°C for 12 minutes, and cool to obtain a core layer mixture;

[0069] The core layer mixture is added into the main conical twin-screw extruder, and the skin layer mixture is added into the auxiliary conical twin-screw extruder, and extruded, cooled, pulled and cut at the same time to obtain a PVC board;

[0070] The skin layer mixture comprises the following ingredients, by weight: 80 parts of PVC resin A, 3 parts of hyperbranched polyamide ester, 5 parts of chlorinated polyethylene, 0.6 parts of oxidized polyethylene wax, 0.3 parts of zinc stearate, 3 parts of hydrotalcite, and 8 parts of calcium sulfate whisker-graphene composite;

[0071] The core layer mixture includes the following components, by weight: 70 parts of PVC resin B, 5 parts of chlorinated polyethylene, 20 parts of calcium carbonate, 3 parts of hydrotalcite, 2 parts of azodicarbonamide, 0.6 parts of oxidized polyethylene wax, and 0.3 parts of zinc stearate.

[0072] Comparative Example 1: No chitosan was used for intercalation treatment, and the rest was the same as Example 1:

[0073] Step 1: Preparation of hyperbranched polyamide ester:

[0074] Take 5.5g of diethanolamine and 15mL of N,N-dimethylacetamide, stir evenly to obtain a diethanolamine solution; take 7g of succinic anhydride and 15mL of N,N-dimethylacetamide, stir evenly, pass nitrogen, then add the diethanolamine solution at 0°C, react for 9h, and obtain compound A; take 10g of compound A, add 0.2g of p-toluenesulfonic acid, react at 122°C for 7.5h, extract, stand, and dry to obtain hyperbranched polyamide ester;

[0075] Step 2: Preparation of graphene loaded with ferroferric oxide:

[0076] Take 0.2 g of graphene oxide and 200 mL of deionized water, disperse by ultrasonication, add 1.2 g of ferric chloride hexahydrate and 0.65 g of ferrous sulfate heptahydrate, heat to 62 ° C under nitrogen protection, add 25% ammonia water, adjust the pH value to 9.5, heat to 67 ° C, react for 4 h, wash and dry to obtain graphene loaded with ferrosoferric oxide;

[0077] Step 3: Preparation of calcium sulfate whisker-nano copper composite:

[0078] Take 3g of calcium sulfate whisker, 35mL of deionized water, and 1g of anhydrous ethanol, stir evenly, heat to 57°C, add 25% ammonia water, adjust the pH value to 8.5, add 0.5g of γ-aminopropyltriethoxysilane, react for 1.5h, heat to 82°C, react for 1.5h, cool to 42°C, add 3.5mL of 0.8mol / L copper sulfate solution, react for 1.5h, filter, add 100mL of deionized water, stir evenly, heat to 72°C, add 10mol / L of sodium hydroxide solution, adjust the pH value to 10, add 1g of hydrazine hydrate, react for 1.5h, filter, wash, and dry to obtain a calcium sulfate whisker-nano copper composite;

[0079] Step 4: Preparation of calcium sulfate whisker-graphene composite:

[0080] Take 0.1 g of graphene loaded with ferroferric oxide and 200 mL of deionized water, disperse by ultrasonication, add 2 g of calcium sulfate whisker-nano copper composite, stir evenly, heat to 62° C., react for 4.5 h, wash and dry to obtain a calcium sulfate whisker-graphene composite;

[0081] Step 5: Preparation of PVC board:

[0082] PVC resin A, hyperbranched polyamide ester, chlorinated polyethylene, oxidized polyethylene wax, zinc stearate, hydrotalcite, and calcium sulfate whisker-graphene composite were stirred at 82° C. for 28 min and cooled to obtain a skin layer mixture;

[0083] Take PVC resin B, chlorinated polyethylene, calcium carbonate, hydrotalcite, azodicarbonamide, oxidized polyethylene wax, and zinc stearate, stir at 92°C for 11 minutes, and cool to obtain a core layer mixture;

[0084] The core layer mixture is added into the main conical twin-screw extruder, and the skin layer mixture is added into the auxiliary conical twin-screw extruder, and extruded, cooled, pulled and cut at the same time to obtain a PVC board;

[0085] The skin layer mixture comprises the following ingredients, by weight: 75 parts of PVC resin A, 2.5 parts of hyperbranched polyamide ester, 4.5 parts of chlorinated polyethylene, 0.4 parts of oxidized polyethylene wax, 0.2 parts of zinc stearate, 2.5 parts of hydrotalcite, and 7.5 parts of calcium sulfate whisker-graphene composite;

[0086] The core layer mixture includes the following components, by weight: 67 parts of PVC resin B, 4.5 parts of chlorinated polyethylene, 18 parts of calcium carbonate, 2.5 parts of hydrotalcite, 1.5 parts of azodicarbonamide, 0.4 parts of oxidized polyethylene wax, and 0.2 parts of zinc stearate.

[0087] Comparative Example 2: No hyperbranched polyamide was added, and the rest was the same as Example 1:

[0088] Step 1: Preparation of modified graphene oxide:

[0089] Take 0.2 g of graphene oxide and 200 mL of deionized water, disperse by ultrasonication, add 1.2 g of ferric chloride hexahydrate and 0.65 g of ferrous sulfate heptahydrate, heat to 62 ° C under nitrogen protection, add 25% ammonia water, adjust the pH value to 9.5, heat to 67 ° C, react for 4 h, wash and dry to obtain graphene loaded with ferrosoferric oxide;

[0090] Take 0.2g of graphene loaded with ferroferric oxide and 100mL of deionized water, and disperse them by ultrasonication to obtain a graphene solution loaded with ferroferric oxide; take 0.3g of chitosan and 20mL of deionized water, stir evenly, drop 0.2mL of 36% hydrochloric acid, stir for 35min, drop ammonia water, adjust the pH value to 3.8, add the graphene solution loaded with ferroferric oxide, heat to 58°C, react for 1.5h, wash and dry to obtain modified graphene oxide;

[0091] Step 2: Preparation of calcium sulfate whisker-nano copper composite:

[0092] Take 3g of calcium sulfate whisker, 35mL of deionized water, and 1g of anhydrous ethanol, stir evenly, heat to 57°C, add 25% ammonia water, adjust the pH value to 8.5, add 0.5g of γ-aminopropyltriethoxysilane, react for 1.5h, heat to 82°C, react for 1.5h, cool to 42°C, add 3.5mL of 0.8mol / L copper sulfate solution, react for 1.5h, filter, add 100mL of deionized water, stir evenly, heat to 72°C, add 10mol / L of sodium hydroxide solution, adjust the pH value to 10, add 1g of hydrazine hydrate, react for 1.5h, filter, wash, and dry to obtain a calcium sulfate whisker-nano copper composite;

[0093] Step 3: Preparation of calcium sulfate whisker-graphene composite:

[0094] Take 0.1 g of modified graphene oxide and 200 mL of deionized water, disperse by ultrasonication, add 2 g of calcium sulfate whisker-nano copper composite, stir evenly, heat to 62° C., react for 4.5 h, wash and dry to obtain a calcium sulfate whisker-graphene composite;

[0095] Step 4: Preparation of PVC board:

[0096] PVC resin A, chlorinated polyethylene, oxidized polyethylene wax, zinc stearate, hydrotalcite, and calcium sulfate whisker-graphene composite were stirred at 82° C. for 28 min and cooled to obtain a skin layer mixture;

[0097] Take PVC resin B, chlorinated polyethylene, calcium carbonate, hydrotalcite, azodicarbonamide, oxidized polyethylene wax, and zinc stearate, stir at 92°C for 11 minutes, and cool to obtain a core layer mixture;

[0098] The core layer mixture is added into the main conical twin-screw extruder, and the skin layer mixture is added into the auxiliary conical twin-screw extruder, and extruded, cooled, pulled and cut at the same time to obtain a PVC board;

[0099] The skin layer mixture includes the following components, by weight: 75 parts of PVC resin A, 4.5 parts of chlorinated polyethylene, 0.4 parts of oxidized polyethylene wax, 0.2 parts of zinc stearate, 2.5 parts of hydrotalcite, and 7.5 parts of calcium sulfate whisker-graphene composite;

[0100] The core layer mixture includes the following components, by weight: 67 parts of PVC resin B, 4.5 parts of chlorinated polyethylene, 18 parts of calcium carbonate, 2.5 parts of hydrotalcite, 1.5 parts of azodicarbonamide, 0.4 parts of oxidized polyethylene wax, and 0.2 parts of zinc stearate.

[0101] Comparative Example 3: No nano copper is loaded, and the rest is the same as Example 1:

[0102] Step 1: Preparation of hyperbranched polyamide ester:

[0103] Take 5.5g of diethanolamine and 15mL of N,N-dimethylacetamide, stir evenly to obtain a diethanolamine solution; take 7g of succinic anhydride and 15mL of N,N-dimethylacetamide, stir evenly, pass nitrogen, then add the diethanolamine solution at 0°C, react for 9h, and obtain compound A; take 10g of compound A, add 0.2g of p-toluenesulfonic acid, react at 122°C for 7.5h, extract, stand, and dry to obtain hyperbranched polyamide ester;

[0104] Step 2: Preparation of modified graphene oxide:

[0105] Take 0.2 g of graphene oxide and 200 mL of deionized water, disperse by ultrasonication, add 1.2 g of ferric chloride hexahydrate and 0.65 g of ferrous sulfate heptahydrate, heat to 62 ° C under nitrogen protection, add 25% ammonia water, adjust the pH value to 9.5, heat to 67 ° C, react for 4 h, wash and dry to obtain graphene loaded with ferrosoferric oxide;

[0106] Take 0.2g of graphene loaded with ferroferric oxide and 100mL of deionized water, and disperse them by ultrasonication to obtain a graphene solution loaded with ferroferric oxide; take 0.3g of chitosan and 20mL of deionized water, stir evenly, drop 0.2mL of 36% hydrochloric acid, stir for 35min, drop ammonia water, adjust the pH value to 3.8, add the graphene solution loaded with ferroferric oxide, heat to 58°C, react for 1.5h, wash and dry to obtain modified graphene oxide;

[0107] Step 3: Preparation of modified calcium sulfate whiskers:

[0108] Take 3g of calcium sulfate whiskers, 35mL of deionized water, and 1g of anhydrous ethanol, stir evenly, heat to 57°C, add 25% ammonia water dropwise, adjust the pH value to 8.5, add 0.5g of γ-aminopropyltriethoxysilane, react for 1.5h, heat to 82°C, react for 1.5h, filter, wash, and dry to obtain modified calcium sulfate whiskers;

[0109] Step 4: Preparation of calcium sulfate whisker-graphene composite:

[0110] Take 0.1 g of modified graphene oxide and 200 mL of deionized water, disperse by ultrasonication, add 2 g of modified calcium sulfate whisker, stir evenly, heat to 62° C., react for 4.5 h, wash and dry to obtain a calcium sulfate whisker-graphene composite;

[0111] Step 5: Preparation of PVC board:

[0112] PVC resin A, hyperbranched polyamide ester, chlorinated polyethylene, oxidized polyethylene wax, zinc stearate, hydrotalcite, and calcium sulfate whisker-graphene composite were stirred at 82° C. for 28 min and cooled to obtain a skin layer mixture;

[0113] Take PVC resin B, chlorinated polyethylene, calcium carbonate, hydrotalcite, azodicarbonamide, oxidized polyethylene wax, and zinc stearate, stir at 92°C for 11 minutes, and cool to obtain a core layer mixture;

[0114] The core layer mixture is added into the main conical twin-screw extruder, and the skin layer mixture is added into the auxiliary conical twin-screw extruder, and extruded, cooled, pulled and cut at the same time to obtain a PVC board;

[0115] The skin layer mixture comprises the following ingredients, by weight: 75 parts of PVC resin A, 2.5 parts of hyperbranched polyamide ester, 4.5 parts of chlorinated polyethylene, 0.4 parts of oxidized polyethylene wax, 0.2 parts of zinc stearate, 2.5 parts of hydrotalcite, and 7.5 parts of calcium sulfate whisker-graphene composite;

[0116] The core layer mixture includes the following components, by weight: 67 parts of PVC resin B, 4.5 parts of chlorinated polyethylene, 18 parts of calcium carbonate, 2.5 parts of hydrotalcite, 1.5 parts of azodicarbonamide, 0.4 parts of oxidized polyethylene wax, and 0.2 parts of zinc stearate.

[0117] experiment:

[0118] The PVC boards prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were cut into 180 mm × 60 mm × 4 mm specimens for performance testing. The tensile strength was tested to characterize the mechanical properties, and the limiting oxygen index was tested to characterize the flame retardancy. The obtained data are shown below:

[0119]

[0120] Conclusion: From the comparison of the data in the table, it can be seen that in Comparative Example 1, chitosan is not used for intercalation treatment, the interlayer spacing of graphene is small, the calcium sulfate whisker-nano copper composite that can be loaded is reduced, and the mechanical properties and flame retardancy of the PVC board are reduced. In Comparative Example 2, hyperbranched polyamide ester is not added, the mechanical properties of the PVC board are reduced, the compatibility of the calcium sulfate whisker-graphene composite in the mixture deteriorates, and the flame retardancy is also reduced. The mechanical properties and flame retardancy of the PVC board without nano-copper loading in Comparative Example 3 are reduced. Examples 1-3 of the present invention use chitosan for intercalation treatment, which increases the interlayer spacing of the graphene loaded with ferroferric oxide, so that it has more specific surface area to load the calcium sulfate whisker-nano copper composite, improves the dispersibility of the calcium sulfate whisker-nano copper composite, and thus enhances the mechanical properties and flame retardancy of the PVC board. The hyperbranched polyamide ester is used to modify the PVC resin, thereby enhancing the mechanical properties of the PVC resin and also enhancing the compatibility of the calcium sulfate whisker-graphene composite in the mixture, thereby enhancing the mechanical properties and flame retardancy of the PVC board.

[0121] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A preparation process for a calcium sulfate whisker reinforced PVC board, characterized in that: The following steps are involved: Step 1: Take modified graphene oxide and deionized water, perform ultrasonic dispersion, add calcium sulfate whisker-nano copper composite, stir evenly, heat to 60-65° C., react for 4-5 hours, wash and dry to obtain calcium sulfate whisker-graphene composite; Step 2: taking PVC resin A, hyperbranched polyamide ester, chlorinated polyethylene, oxidized polyethylene wax, zinc stearate, hydrotalcite, and calcium sulfate whisker-graphene composite, stirring at 80-85° C. for 25-30 min, and cooling to obtain a skin layer mixture; Step 3: Take PVC resin B, chlorinated polyethylene, calcium carbonate, hydrotalcite, azodicarbonamide, oxidized polyethylene wax, and zinc stearate, stir at 90-95° C. for 10-12 minutes, and cool to obtain a core layer mixture; Step 4: extruding, cooling, pulling and cutting the core layer mixture and the skin layer mixture at the same time to obtain a PVC board; The preparation method of the modified graphene oxide is as follows: taking graphene loaded with ferroferric oxide and deionized water, ultrasonically dispersing to obtain a graphene solution loaded with ferroferric oxide; taking chitosan and deionized water, stirring evenly, dripping hydrochloric acid, stirring for 30-40 minutes, dripping ammonia water, adjusting the pH value to 3.5-4, adding the graphene solution loaded with ferroferric oxide, heating to 55-60° C., reacting for 1-2 hours, washing, and drying to obtain the modified graphene oxide.

2. A process for preparing a calcium sulfate whisker reinforced PVC board according to claim 1, characterized in that: The preparation method of the calcium sulfate whisker-nano copper composite comprises the following steps: taking calcium sulfate whisker, deionized water and anhydrous ethanol, stirring evenly, heating to 55-60° C., dripping ammonia water, adjusting the pH value to 8-9, adding γ-aminopropyltriethoxysilane, reacting for 1-2 hours, heating to 80-85° C., reacting for 1-2 hours, cooling to 40-45° C., adding copper sulfate solution, reacting for 1-2 hours, filtering, adding deionized water, stirring evenly, heating to 70-75° C., dripping sodium hydroxide solution, adjusting the pH value to 10, adding hydrazine hydrate, reacting for 1-2 hours, filtering, washing and drying to obtain the calcium sulfate whisker-nano copper composite.

3. The preparation process of a calcium sulfate whisker reinforced PVC board according to claim 1, characterized in that: The preparation method of the graphene loaded with ferroferric oxide is as follows: graphene oxide and deionized water are taken, ultrasonically dispersed, ferric chloride hexahydrate and ferrous sulfate heptahydrate are added, the temperature is raised to 60-65° C. under nitrogen protection, ammonia water is added dropwise, the pH value is adjusted to 9-10, the temperature is heated to 65-70° C., the reaction is carried out for 3-5 hours, and the graphene loaded with ferroferric oxide is obtained by washing and drying.

4. A process for preparing a calcium sulfate whisker reinforced PVC board according to claim 1, characterized in that: The preparation method of the hyperbranched polyamide ester comprises the following steps: taking diethanolamine and N,N-dimethylacetamide, stirring evenly to obtain a diethanolamine solution; taking succinic anhydride and N,N-dimethylacetamide, stirring evenly, passing nitrogen, and then adding the diethanolamine solution at 0-1°C, reacting for 8-10 hours to obtain a compound A; taking the compound A, adding p-toluenesulfonic acid, reacting at 120-125°C for 7-8 hours, extracting, standing, and drying to obtain a hyperbranched polyamide ester.

5. The preparation process of a calcium sulfate whisker reinforced PVC board according to claim 1, characterized in that: The skin layer mixture comprises the following components, by weight: 70-80 parts of PVC resin A, 2-3 parts of hyperbranched polyamide ester, 4-5 parts of chlorinated polyethylene, 0.2-0.6 parts of oxidized polyethylene wax, 0.1-0.3 parts of zinc stearate, 2-3 parts of hydrotalcite, and 7-8 parts of calcium sulfate whisker-graphene composite.

6. A process for preparing a calcium sulfate whisker reinforced PVC board according to claim 1, characterized in that: The core layer mixture comprises the following components, by weight: 65-70 parts of PVC resin B, 4-5 parts of chlorinated polyethylene, 15-20 parts of calcium carbonate, 2-3 parts of hydrotalcite, 1-2 parts of azodicarbonamide, 0.2-0.6 parts of oxidized polyethylene wax, and 0.1-0.3 parts of zinc stearate.

7. A calcium sulfate whisker reinforced PVC board prepared according to the preparation process of a calcium sulfate whisker reinforced PVC board according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Calcium sulfate whisker reinforced resin grinding wheel and preparation method thereof

    CN104669131A

  • Modified calcium sulphate crystal whisker as well as preparation method and application thereof

    CN108003386A